Purchasing Professionals in State Government: How Ethical Are They? - Laura B. Forker (Journal of Business Ethics, 1990)
A survey of purchasing professionals in the Arizona state government was conducted to determine how familiar the buyers were with the Arizona laws regarding ethical conduct, what ethical standards they followed in purchasing, and what types of ethical dilemmas they faced in their work. The findings indicate that no serious ethical problems exist among the respondents. Employees in the centralized purchasing office seemed to act somewhat more ethically than buyers in peripheral offices, however.
Keywords: 330; Government purchasing; Ethics